2018
DOI: 10.1002/uog.17476
|View full text |Cite
|
Sign up to set email alerts
|

Fetal myocardial performance index in assessment and management of small‐for‐gestational‐age fetus: a cohort and nested case–control study

Abstract: MPI did not demonstrate clinical utility in either triage or longitudinal follow-up of an SGA/FGR cohort presenting to fetal medicine services. Given that prior research suggesting its utility originates from single-center cohorts, while multicenter, large cohorts have suggested little utility or no additional utility if routine UA/MCA/DV Doppler is performed, publication bias may have affected previous reports. It seems unlikely that MPI has clinical utility in assessment and management of SGA/FGR fetuses. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 53 publications
(91 reference statements)
8
11
3
3
Order By: Relevance
“…Previous studies have demonstrated that pathological conditions that could influence cardiac functions also alter the Mod-MPI values. [5][6][7][8][9][10][11][12][13][14][15] In the present study, all of the UA S/D values were in the normal ranges based on GA. Therefore, we could not interpret this result objectively.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have demonstrated that pathological conditions that could influence cardiac functions also alter the Mod-MPI values. [5][6][7][8][9][10][11][12][13][14][15] In the present study, all of the UA S/D values were in the normal ranges based on GA. Therefore, we could not interpret this result objectively.…”
Section: Discussionsupporting
confidence: 56%
“…Fetal growth restriction, twin-twin transfusion syndrome, maternal diabetes, preeclampsia, fetal hydrops, fetal anemia, and cholestasis are examples of these conditions. [5][6][7][8][9][10][11][12][13][14][15] MPI values may be a guide for fetal interference and timing of the delivery in cases that affect cardiac function. However, it is important to ensure that the measurement of MPI is consistent and accurate.…”
mentioning
confidence: 99%
“…There were no significant correlations between the left MPI and adverse perinatal outcomes. Exploratory subgroup comparisons revealed only minor differences in MPI, reaching statistical significance, only in the EFW<3 rd vs 3 rd -10 th centile comparison [23] . Our study in contrast, revealed that 87.5% of fetuses had an abnormal MPI value [more than 95 th centile].…”
Section: Discussionmentioning
confidence: 77%
“…Nassr et al showed that MPI was a potentially useful tool which was crucial in classifying FGR pregnancies and predicting neonatal outcome. However, Henry et al monitored 38 early‐onset and 14 late‐onset FGR fetuses and concluded that MPI was not of clinical value in assessment and management of SGA/FGR fetuses. Pacheco et al monitored 24 appropriate growth fetuses, 30 fetuses with EFW between the 3rd and 10th centiles, and 22 fetuses with EFW < 3rd centile and also showed that MPI was not significantly different between fetuses with appropriate GA and those with growth restriction.…”
Section: Discussionmentioning
confidence: 99%